ظاهرة الاغتراب ووصف الصحراء عند شعراء الجنوب الجزائري - بريم, صباح; بن خويا, إدريس (جامعة الوادي - university of Eloued, 2021)
تعد ظاهرة الاغتراب واحدة من أبرز القضايا البارزة على الساحة الأدبية المعاصرة، كانعكاس للتغيرات الحاصلة في النظام الاجتماعي والسياسي والاقتصادي والثقافي...، وما خلفه ذلك على ذات المبدع. ومن خلال هذه الورقة البحثية سنرى علاقة الاغتراب بصورة الصحراء. هذه الأخيرة التي تحظى بمكانة بارزة وبحضور مميز عند شعراء الجنوب الجزائري، و انحصار وجودها وتلاشي الكثير من ملامحها في الحياة اليومية، هو ما يجعلها ترتبط بحالة الاغتراب بشكل وثيق. Abstract The phenomenon of alienation is considered one of the most prominent issues in the contemporary literary scene. It reflects the changes taking place in the social, political, economic and cultural system and their impact on the poet himself. Through this research paper, we will highlight the relationship of alienation with the image of the Sahara which has a distinguished presence among the South Algerian poets in spite of its limited existence and the disappearance of some of its features in daily life. This makes it closely related to the state/feeling of alienation.
مقال
Keywords: صورة الصحراء. الاغتراب. الجنوب الجزائري. الاغتراب الذاتي. الاغتراب الاجتماعي. الاغتراب الوجودي; key words Desert image, Alienation, South Algerian poets, Self-alienation. Social alienation, Existential alienation.